Perlindungan Hukum Terhadap Korban Tindak Pidana dalam Konsep Pemaafan Hakim (Perbandingan antara Hukum Pidana Indonesia dengan Belanda) - Muhammad Gibran Hariza; Syarif Nurhidayat (Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract This research aims to analyze the concept of judicial discretion as regulated in the National Criminal Code and compare it with the Dutch Criminal Code from the perspective of legal protection for victims of criminal acts. The issues examined in this study are: First, the basic idea of judicial discretion as related to provisions for victim protection. Second, a comparison with the Dutch legal system. The method used in this study is a normative method using a regulatory, comparative, and conceptual approach with primary, secondary, and tertiary legal data sources obtained through document and library studies and analyzed descriptively and qualitatively. Based on the results of the study, the concept of judicial leniency to be implemented in the criminal justice system in Indonesia is not yet fully supported by factors related to legal protection for victims. Additionally, there is no explicit explanation regarding the classification of criminal offenses that may be subject to leniency and the clarification of sentencing criteria that should serve as a guideline for judges in rendering decisions. The Netherlands, with its advanced criminal justice system, has long since implemented the concept of judicial discretion with mutually supportive integration between norms, so that the interests of victims' rights can be fulfilled. This can be an innovation in the reform of the criminal justice system in Indonesia. The recommendation from this research is that there is a need for improvement, synchronization, and harmonization of the provisions in the concept of judicial discretion. Additionally, victim impact statements can be considered as one of the factors to accommodate the interests of victims of criminal offenses.